Pengaruh Lingkungan Sekolah terhadap Pembentukan Karakter Siswa Kelas V SD Inpres 3 Tondo: The Influence of the School Environment on Character Formation of Fifth-Grade Students at SD Inpres 3 Tondo - Grafindia Dungga; Yusdin Bin M. Gagaramusu; Surahman Surahman; Nashrullah Nashrullah; Ammar Abdullah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to determine the influence of the school environment on the character formation of fifth-grade students of SD Inpres 3 Tondo. The main problem underlying this study is the indication of students' behavior that is less disciplined, less responsible, and less respectful of teachers and peers while in the school environment. This type of research is quantitative research using an experimental design, a One-Group Pretest and Posttest Design. The population in this study was all fifth-grade students of SD Inpres 3 Tondo, totaling 32 people, with a sampling technique using saturated sampling (the entire population was sampled). Data collection techniques were carried out through questionnaires, observations, and interviews. Data analysis was carried out descriptively and inferentially using the Shapiro-Wilk normality test and the Paired Sample T-Test hypothesis test with the help of the IBM SPSS program. The results of the descriptive analysis showed an increase in the average (mean) value of student character from 102.31 at the pretest to 106.56 at the posttest after being given treatment in the form of strengthening a conducive school environment. Based on the normality test, the pretest data (Sig. 0.777 > 0.05) and posttest (Sig. 0.301 > 0.05) were declared normally distributed. The results of the Paired Sample T-Test showed a calculated t value of -2.181 with a significance level of 0.037. Because the significance value is smaller than the 0.05 level (0.037 < 0.05), H0 is rejected, and Ha is accepted. This proves that there is a significant influence of the school environment on the character formation of fifth-grade students of SD Inpres 3 Tondo. This success is supported by positive habits, consistent implementation of rules, and role models provided by teachers at school.